Sufis And Women: The Study of Women’s Sufis In The Western World - Ariani Barroroh Baried; Mulawarman Hannase (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2022)
The lack of records about the involvement and contribution of women in Sufism texts cannot be used as an excuse that women have a small role and position in the development and dissemination of Sufism teachings, doctrines, and practices. Of the two female Sufi names, namely Rabi’ah and Aishah al-Ba’uniyyah, two big names prove that women have equal opportunities in achieving spiritual knowledge. Therefore, the writer is interested in female Sufis, especially in Western countries, where so far, many writers have focused on female Sufis in the eastern world, therefore it is very interesting to study female Sufis in the Western world and to answer questions. about; Aren’t their women in the world of Sufism? Is it true that the world of Sufism belongs entirely to men only? This paper is a paper using a qualitative descriptive approach. The author uses a literature review with the data sources used in this paper are secondary data originating from the literature such as books, journals, articles, and various sources relevant to the theme of the discussion in this paper. The results of the study describe female Sufis, namely Hajjah Amina Adil and Hajjah Naziha Adil with their organization called HNCO (Hajjah Naziha Charitable Organization) engaged in philanthropy. Then another female Sufi is Nahid Angha who is known as one of the founders of the International Sufi Woman Organization, a world Sufi women’s organization. This organization is concerned with peace programs and women’s empowerment.